Metropolisation and the Metropolitan Space: The Practice of Horizontal Partnerships at Local Level - Dan - Ionut Istrate; Ciprian Alupului (CES Working Papers, 2012)
At present, the development of large cities raises problems to specialists, who must find solutions to the most diverse processes of concentration, to the numerous problems of the communities tightly connected with the metropolitan areas / growth poles. The formation of the metropolitan areas regards not only the most common issues related to the increase of the standard of living, but also the concrete ways of solving the crises and reducing the forms related to the current metropolitan issues. The objective of this article is to present the main favourable aspects of the metropolisation processes, pointing out the advantages of implementing such areas in Romania.
Keywords: R10; R11; 330; metropolisation; development; territory; metropolitan areas; governance Romania